Anchored PKA as a gatekeeper for gap junctions - Pidoux, Guillaume (Commun Integr Biol, 2015)
Anchored protein kinase A (PKA) bound to A Kinase Anchoring Protein (AKAP) mediates effects of localized increases in cAMP in defined subcellular microdomains and retains the specificity in cAMP-PKA signaling to distinct extracellular stimuli. Gap junctions are pores between adjacent cells constituted by connexin proteins that provide means of communication and transfer of small molecules. While the PKA signaling is known to promote human trophoblast cell fusion, the gap junction communication through connexin 43 (Cx43) is a prerequisite for this process. We recently demonstrated that trophoblast fusion is regulated by ezrin, a known AKAP, which binds to Cx43 and delivers PKA in the vicinity gap junctions. We found that disruption of the ezrin-Cx43 interaction abolished PKA-dependent phosphorylation of Cx43 as well as gap junction communication and subsequently cell fusion. We propose that the PKA-ezrin-Cx43 macromolecular complex regulating gap junction communication constitutes a general mechanism to control opening of Cx43 gap junctions by phosphorylation in response to cAMP signaling in various cell types.